2015
DOI: 10.1080/00958972.2015.1050005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and catalytic properties of an iron(III) complex supported by amine-bis(phenolate) ligand

Abstract: 2015) Synthesis and catalytic properties of an iron(III) complex supported by amine-bis(phenolate) O ClThe reaction of FeCl 3 with 2-tetrahydrofuranylamino-N,N-bis(2-methylene-4-ethyl-6-tert-butylphenol), H 2 [O 3 N] BuEtTHF (H 2 L) affords a new iron(III) complex, [LFeCl] 1, whose structure has been determined by X-ray crystallography. Electrochemical studies show that 1 can electrocatalyze hydrogen evolution both from acetic acid with a turnover frequency (TOF) of 39.98 mol of hydrogen per mole of catalyst p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Chelation with related tetradentate tripodal ligands gives Fe14 and Fe15 , which are also active in aqueous media. , CV of Fe14 in DMF shows two features assigned as sequential one-electron reductions of the iron center, and addition of AcOH leads to an E onset that coincides with the Fe 2+ /Fe + redox wave . CPE in aqueous phosphate solution (pH 7.0) with a GC WE at E onset = −1.50 V vs Ag/AgNO 3 produced a FE H2 of 93% over 1 h (TON H2 = 141).…”
Section: Homogeneous Catalysismentioning
confidence: 98%
See 2 more Smart Citations
“…Chelation with related tetradentate tripodal ligands gives Fe14 and Fe15 , which are also active in aqueous media. , CV of Fe14 in DMF shows two features assigned as sequential one-electron reductions of the iron center, and addition of AcOH leads to an E onset that coincides with the Fe 2+ /Fe + redox wave . CPE in aqueous phosphate solution (pH 7.0) with a GC WE at E onset = −1.50 V vs Ag/AgNO 3 produced a FE H2 of 93% over 1 h (TON H2 = 141).…”
Section: Homogeneous Catalysismentioning
confidence: 98%
“…Longer CPE experiments showed that the current remains stable for at least 40 h . In contrast, complex Fe15 has an additional reductive feature in CV scans and is thought to be catalytically active as an Fe 0 species . Despite this, E onset occurs at a similar value to Fe14 .…”
Section: Homogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, four-coordinate copper­(I) complexes with two bidentate ligands (bisimine and/or bisphosphine ligands) have attracted increased interest as dopants due to the low price and consistent availability of copper metal . In order to reduce the electrostatic repulsion, the ground-state geometry of Cu­(I) complexes favors a (distorted) tetrahedral arrangement of the ligands around the copper center. , Upon light excitation, a metal-to-ligand charge transfer (MLCT) transition from the 3d orbital of Cu­(I) to the π*-orbital of the surrounding diimine ligand takes place. We can modify the photophysical and electrochemical properties across a wide range due to the intrinsic structural diversity of the underlying diimine ligands. For the higher emission complexes, the use of sterically packed ligands provides a strict environment surrounding the copper center.…”
Section: Introductionmentioning
confidence: 99%